Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) pada Kurikulum Merdeka di TPA Raudhotul Jannah - Muhassanah, Nur'aini; Muhammad Nur Rizal; Siti Inayah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2024)
The Project for Strengthening the Profile of Pancasila students is a new paradigm for the independent curriculum. In the Project for Strengthening the Pancasila Student Profile (P5), there are several dimensions that are important to pay attention to. These dimensions include aspects of character that must be considered in an effort to strengthen students' understanding and practice of Pancasila values. The first dimension of character is Faith and Piety, Independence, Collaboration, Global Diversity, Critical Reasoning and Creative. Character education should start from an early age. This research aims to determine the implementation of the Pancasila Student Profile Strengthening Project (P5) and the impact of its implementation on the six dimensions of student profile character in PAUD. The research method used is a qualitative case study type with data collection techniques using observation, interviews and documentation. The research results show that the implementation of P5 at the TPA Raodhatul Jannah has been carried out with the theme